2007
DOI: 10.1186/1476-8518-5-5
|View full text |Cite
|
Sign up to set email alerts
|

IMP321 (sLAG-3), an immunopotentiator for T cell responses against a HBsAg antigen in healthy adults: a single blind randomised controlled phase I study

Abstract: Background: LAG-3 (CD223) is a natural high affinity ligand for MHC class II. The soluble form (sLAG-3) induces maturation of monocyte-derived dendritic cells in vitro and is used as a potent Th1-like immune enhancer with many antigens in animal models. To extend this observation to human, a proof of concept study was conducted with a clinical-grade sLAG-3, termed IMP321, coinjected with alum-non-absorbed recombinant hepatitis B surface antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…PBMCs were incubated with or without IMP321 (1 g/ml) or TLR agonists (optimal concentrations): TLR1-2, TLR3, TLR4, TLR5, TLR6-2, TLR7-8, or TLR9 agonists for 24 thrombosis due to platelet activation (38) but CD40 agonist therapeutic Abs are now being tested in cancer patients. IMP321 has been shown to be safe and well-tolerated in several phase I/II trials (www.clinicaltrials.gov/) (24,39) and immunomonitoring will reveal whether some of the effector cell subsets described in the present study are indeed activated in vivo.…”
Section: Figure 6 Specific and Indirect Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…PBMCs were incubated with or without IMP321 (1 g/ml) or TLR agonists (optimal concentrations): TLR1-2, TLR3, TLR4, TLR5, TLR6-2, TLR7-8, or TLR9 agonists for 24 thrombosis due to platelet activation (38) but CD40 agonist therapeutic Abs are now being tested in cancer patients. IMP321 has been shown to be safe and well-tolerated in several phase I/II trials (www.clinicaltrials.gov/) (24,39) and immunomonitoring will reveal whether some of the effector cell subsets described in the present study are indeed activated in vivo.…”
Section: Figure 6 Specific and Indirect Cd8mentioning
confidence: 99%
“…The percentages of CD3 ϩ CD4 ϩ , CD3 ϩ CD8 ϩ T cells, and CD3 Ϫ CD8 ϩ NK cells expressing one, two, or three of these cytokines were determined. The measurement of cytokine ϩ cells using this procedure has been validated previously and gives an overall coefficient of variation Ͻ20% after Ag-specific stimulation (24). A slight increase in cytokine-expressing CD4 ϩ T cells was detected in 44 (of 60) PBMCs stimulated with IMP321 compared with medium alone.…”
Section: Imp321 Induces Cd8 ϩ T Cells and Nk Cells To Produce Cytokinmentioning
confidence: 99%
“…CD40L has been tested in phase I trials (4) but clinical development has been stopped due to secondary effects such as thrombosis induction (its receptor, CD40, is also expressed on platelets and endothelial cells). Thus, the soluble LAG-3Ig fusion protein (or IMP321) is the only protein that is presently available for this therapeutic approach (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The safety and toxicity profile of IMP321 has been established in two randomized phase I trials of subcutaneous vaccination against Influenza virus (Flu, n ¼ 60) and the Hepatitis virus (HBsAg, n ¼ 48) in healthy volunteers (14,15). Both studies revealed very good clinical tolerability with a low toxicity profile for the four dose levels of IMP321: 3, 10, 30, and 100 mg. Mage-A3/DP4-specific CD4 T-cells from patient Lau 1187 showing two phenotypes with tetramer-high and tetramer-low staining.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it enhances specific immune responses, by stimulation of antigen cross presentation to CD8 T-cells, and by decreasing regulatory T-cell frequency and function (9). Clinical trials with IMP321 showed already promising results when used as adjuvant for vaccination against hepatitis B and influenza viruses in healthy individuals (14,15). Several trials have provided evidence for clinical activity in patients with advanced renal cell carcinoma, metastatic breast carcinoma, and metastatic melanoma (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%